2019
DOI: 10.3390/ijerph16152668
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness and Cost-Effectiveness of Oral-Health Promotion in Dental Caries Prevention among Children: Systematic Review and Meta-Analysis

Abstract: The objective of this study was to evaluate the clinical effectiveness and cost-effectiveness of oral-health promotion programs (OHPPs) aiming to improve children’s knowledge of favorable oral health behavior to lower decayed/-missing/-filled teeth (DMFT) while reducing the financial cost on health institutions. An electronic search was performed in seven databases. Studies were restricted to human interventions published in English. The search study followed the Preferred Reporting Items for Systematic Review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 28 publications
1
76
0
4
Order By: Relevance
“…La promoción de la salud mejora la calidad de vida pero requiere un compromiso en aras de poner práctica conductas más saludables, esto sólo se puede lograr cuando la promoción de la salud oral se implementa a nivel comunitario incorporando a varios actores (32) . Estudios recientes han demostrado que la educación desde edades tempranas tiene un impacto en la creación de estas conductas protectoras (8,10) .…”
Section: Discussionunclassified
“…La promoción de la salud mejora la calidad de vida pero requiere un compromiso en aras de poner práctica conductas más saludables, esto sólo se puede lograr cuando la promoción de la salud oral se implementa a nivel comunitario incorporando a varios actores (32) . Estudios recientes han demostrado que la educación desde edades tempranas tiene un impacto en la creación de estas conductas protectoras (8,10) .…”
Section: Discussionunclassified
“…However, we observed that the majority of these facilities do not operate any form of health insurance. The National Health Insurance Scheme (NHIS) which is mandatory social health insurance scheme, is expected to provide additional funding for oral healthcare (13). However because dental care is not under primary healthcare, dental clinics do not benefit from capitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, this has not really been actualized in Nigeria (1). The reason for this being that the little resources assigned to the health sector are mainly directed towards life-threatening conditions such as HIV/AIDS, tuberculosis, and malaria rather than dental caries and other oral diseases (12,13). In addition the strategies to improve access documented in the countries oral health policy is yet to be fully implemented (1,13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying the economic implications of dental caries prevention and treatment provides valuable information to decision makers in allocating scarce resources across healthcare systems 6,7 . Sound decision‐making relies on the careful analysis of the programme costs relative to the effects on health outcomes with a comparable alternate 8 .…”
Section: Introductionmentioning
confidence: 99%